Estudo de grampos em cortinas em solos tropicais na cidade de Goiânia - Resende, Carla de (2014)
Retaining structures with nails have been used in recent decades to contain excavation works in several Brazilian cities, including Goiânia. The nails are made of steel bars inserted in inclined or horizontal drilling, with small diameter and involved in cement grout, to ensure the stability of vertical excavations by frictional forces developed in the contact between the soil and nail. Therefore, it is important to understand this friction to design retaining structures. There are lots of calculation methods proposed by many authors to design nails and verify the stability of these structures. The main objective of this work was to review some calculation methods, conduct pullout tests in the field and laboratory tests with samples taken in situ, to evaluate calculation methodologies or parameters that best apply to the soil studied in Goiânia. Among several proposals to estimate the media shear stress in the soil-nail interface (qs) based on SPT, that showed better results in this paper are those from graph lower limit proposed by Ortigão e Palmeira (1997), Springer (2006) and a proposal based on Décourt & Quaresma (1978) to calculate pile lateral friction, using the proper parameter b. Other propositions based on soil type and parameters of the soil that showed good fits were Wong (1995) and Juran et al. (1990). The relation between qs and the shear stress of soil (ts) resulted values between 0,55 and 0,85. Displacement readings were performed during loading and unloading phase, was observed that for small loads, plastic deformations occured in the nail, so is recommended in cases of nail’s numerical analyzes adopt elastic-plastic models. Predictions of nail's elastic deformation, based on piles theory showed good results, however significant plastic deformation occured in nails. The results of shear tests were compared with the pullout tests, indicating that the reduction factor of laboratory results is necessary.